The illusion of choice: barriers faced by mothers with young children in Kazakhstan in re/entering the labour market: an analysis with the concept of defamilisation - Kabylova, Moldir (2025)
This thesis explores women’s experiences when combining motherhood and paid work, and the role that the state, the markets and the family play in this. The theoretical framework is based on the concept of defamilisation in order to explain the extent to which and the way in which three sectors, the state, the labour market and the family, impact the defamilisation of women (Lister, 1994). Mothers of young children, not only in Kazakhstan but in general need support from the state, employers and family (Dugarova, 2016). The state plays a key role not only in ensuring acceptable standards of living for people by decommodifying them from the labour market (Esping- Andersen, 1990; 1999), but it may also provide support to mothers of young children by defamilising them through assistance with childcare and allowing them to have free time to enter paid work (Lister, 1994; Chau and Yu, 2022).